Study on the Dangerous Chemicals Embargoed from Inland Waterway Transport. Issue 1 (August 2020) - Xie, Tiansheng; Han, Chao
Abstract: Safety management of chemicals transport by inland waterways is closely connected with the safety of people's lives and property and the protection of public environmental. This work aims to study how the dangerous chemicals embargoed from inland waterway transport can be designated in China. Firstly, the safety risks and the factors that may cause safety hazards at Yangtze River are investigated. Then, the regulations for dangerous chemicals embargoed from inland waterway transport in different countries are compared. Finally, the rules for the designation of the dangerous chemicals embargoed from inland waterway transport are proposed. This work promotes the understanding of safety management of chemicals transport by inland waterways.